Accreditation Fraud in Brazilian Military Hospitals: Why "Tone at the Top" Matters. Issue 4 (1st October 2016) - Klaus, L.C.O.
ABSTRACT: This article shows under which circumstances fraudulent accreditation can occur in Brazilian military hospitals, calling attention to the tone at the top as a critical aspect of military fraud deterrence – and hence as a critical aspect of this branch of military ethics. The problems allegedly found in Brazilian military health institutions were revealed through in-depth interviews conducted with 29 professionals who reported to work or have worked in a Brazilian military hospital. These fraud allegations were mostly associated with false documentation and procedures designed to give the appearance that legal requirements for accreditation were met and could be traced back to a weak or corrupt "tone at the top" coming from military higher ranks.